A Retrospective Cohort Study on the Prevalence, Risk Factors, and Improvement of Overactive Bladder Symptoms in Women with Pelvic Organ Prolapse - Aimjirakul K; Ng JJ; Saraluck A; Wattanayingcharoenchai R; Mangmeesri P; Manonai J (Dove Medical Press, 2023)
Komkrit Aimjirakul, Jun Jiet Ng, Apisith Saraluck, Rujira Wattanayingcharoenchai, Peeranuch Mangmeesri, Jittima Manonai Department of Obstetrics & Gynaecology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Jun Jiet Ng; Jittima Manonai, Department of Obstetrics & Gynaecology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, 10400, Thailand, Tel +66-2-2012167, Fax +66-2-2011416, Email njjgbb@gmail.com; jittima.man@mahidol.ac.thBackground: Overactive bladder (OAB) symptoms are common in women with pelvic organ prolapse (POP), but the explanation is unclear. It is also uncertain whether OAB symptoms improve or persist after POP reduction. This study aimed to determine the prevalence and risk factors for OAB symptoms in women with POP, and to compare the improvement of OAB symptoms among women in three treatment groups: pelvic floor exercise, pessary, and surgery.Methods: This retrospective cohort study included patients who visited our urogynecology clinic from January 2016 to December 2020. The Pelvic Floor Bother Questionnaire was used to evaluate selected pelvic floor symptoms (OAB and POP). Demographic characteristics and clinical findings, including Pelvic Organ Prolapse Quantification System and number of prolapsed compartments, were analyzed. Univariate and multivariate analyses were conducted to identify risk factors for OAB symptoms in women with POP. Subgroup analyses were performed in 533 patients to evaluate the improvement of OAB symptoms following POP treatment.Results: A total of 754 patients were analyzed. The incidence of OAB symptoms was 70% (533/754) and two-thirds (65%) reported moderate to severe bother. The lowest points of the anterior wall (OR 0.60; 95% CI 0.41- 0.87; p = 0.01), longer perineal body (OR 0.78; 95% CI 0.21- 0.76; p = 0.02), and previous vaginal delivery (OR 2.10; 95% CI 1.14- 3.89; p = 0.02) were identified as significant risk factors. In the subgroup analyses, improvement in OAB symptoms was observed in 36.6% (195/533) of women who underwent POP treatment. Compared with pelvic floor exercise, pessary (OR 1.40; 95% CI 0.94- 2.07; p = 0.10) and surgery (OR 1.30; 95% CI 0.80- 2.12; p = 0.28) had higher odd ratios but the effects were not significant.Conclusion: The prevalence of OAB symptoms in women with POP was high at 70%. Improvement in OAB symptoms was observed in one-third of women who underwent POP treatment. However, there were no significant differences between the treatment methods.Keywords: pelvic organ prolapse, overactive bladder, pelvic floor bother questionnaire, prevalence, risk factors, pessary, surgery